Implementation of Good Governance, Utilization of Information Technology and Reliability of Government Financial Statement - Hadi Jauhari; Yuliana Sari; Evada Dewata (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2019)
The lack of optimal implementation of Good Governance and the use of information technology is thought to affect the quality of government financial reports. For this reason, this research is intended to determine the relationship between the application of Good Governance, the use of information technology and the reliability of the financial statements of the regional government of South Sumatra Province. The study population was employees of 40 Regional Apparatus Organizations in South Sumatra Province. The sampling technique used is purposive sampling, and 120 respondents are obtained consisting of heads of departments, treasurers of offices, administrators of finance or accounting, and staff of finance at the Regional Apparatus Organization of South Sumatra Province. The collection method uses a questionnaire distributed from May-June 2019. The results of the study show that Good Governance does not have a significant effect on the reliability of local government financial reports. On the contrary, the use of information technology has a significant positive effect on the reliability of local government financial reports. The results of this study have implications for the Regional Government of South Sumatra Province as a Good Governance agent in the government to commit and consistently utilize information and accountable technology in transparent financial reporting.